Durability of SARS-CoV-2–Specific T-Cell Responses at 12 Months Postinfection. (21st October 2021) - Lu, Zhongyan; Laing, Eric D; Pena DaMata, Jarina; Pohida, Katherine; Tso, Marana S; Samuels, Emily C; Epsi, Nusrat J; Dorjbal, Batsukh; Lake, Camille; Richard, Stephanie A; Maves, Ryan C; Lindholm, David A; et al.
Abstract: Background: Characterizing the longevity and quality of cellular immune responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enhances understanding of coronavirus disease 2019 (COVID-19) immunity that influences clinical outcomes. Prior studies suggest SARS-CoV-2–specific T cells are present in peripheral blood 10 months after infection. Analysis of the function, durability, and diversity of cellular response long after natural infection, over a range of ages and disease phenotypes, is needed to identify preventative and therapeutic interventions. Methods: We identified participants in our multisite longitudinal, prospective cohort study 12 months after SARS-CoV-2 infection representing a range of disease severity. We investigated function, phenotypes, and frequency of T cells specific for SARS-CoV-2 using intracellular cytokine staining and spectral flow cytometry, and compared magnitude of SARS-CoV-2–specific antibodies. Results: SARS-CoV-2–specific antibodies and T cells were detected 12 months postinfection. Severe acute illness was associated with higher frequencies of SARS-CoV-2–specific CD4 T cells and antibodies at 12 months. In contrast, polyfunctional and cytotoxic T cells responsive to SARS-CoV-2 were identified in participants over a wide spectrum of disease severity. Conclusions: SARS-CoV-2 infection induces polyfunctional memory T cells detectable at 12 months postinfection, with higher frequency noted in those who experienced severe disease. Abstract : Circulating SARS-CoV-2–specific T cells could be measured 12 months postinfection. Severe acute COVID-19 was associated with a higher magnitude of SARS-CoV-2–specific CD4 T cells and a polyfunctional, central memory phenotype predominated across the disease spectrum.